The 2013 Slab‐Wide Kamchatka Earthquake Sequence. Issue 4 (22nd February 2023) - Rousset, B.; Campillo, M.; Shapiro, N. M.; Walpersdorf, A.; Titkov, N.; Chebrov, D. V.
Abstract: Studies of initiation of large earthquakes are usually focused on frictional instabilities occurring in the near vicinity of the future rupture. Possible contributions of long‐distance interactions with large‐scale tectonic instabilities remain unknown. Here we analyze seismic catalogs and geodetic time series during a few months preceding the 2013 M  = 8.3 deep‐focus Okhotsk earthquake. This deep‐focus event is preceded by four intense seismic clusters in the seismogenic zone. GNSS time series in Kamchatka revealed a transient landward motion episode 1 month prior to the mainshock, consistent with an increase of seismogenic zone loading. This transient loading episode is accompanied by a doubling of the intermediate depth seismicity rate suggesting a transient slab pull as the origin. These observations question the constant subducting velocity hypotheses and may have implications in the understanding of the long‐distance along‐slab stress interactions and in their contribution to initiation of large deep‐focus earthquakes. Plain Language Summary: Subduction zone earthquakes are illuminating the dynamics of oceanic plates plunging into the mantle. In this study we analyzed the earthquake activity in the Kamchatka subduction zone before a 620 km deep M  = 8.3 earthquake that happened in 2013. This so‐far largest recorded deep event was preceded by a large number of smaller seisms happening at much shallower depths, between the trench and 100 km depth. The analysis of surface deformation during this episode shows an increased horizontal compression of the Kamchatka peninsula. These observations and associated models together suggest an acceleration of the subduction plunging, interpreted as a mechanical link between the shallow intense seismicity and the large deep event. Key Points: The M  = 8.3 Okhotsk deep‐focus earthquake has been preceded by four intense shallow seismic clusters GNSS times series analysis reveals a transient event in April 2013 coincident in time with a doubling of intermediate‐depth seismicity rate The ensemble of observations suggest a transient acceleration of the slab plunge in the months before the M  = 8.3 mainshock